Antibacterial activity of gallic acid against Shigella flexneri and its effect on biofilm formation by repressing mdoH gene expression. (December 2018) - Kang, Jiamu; Liu, Liu; Liu, Meihui; Wu, Xiaoxia; Li, Jianke
Abstract: Persistent bacterial infections caused by biofilm-associated Shigella spp. are a global public health concern. The following study aims to determine the antibacterial activity and possible mechanism that gallic acid (GA) displays against Shigella flexneri ( Sh. flexneri ) and its effect on the biofilm formation. The minimum inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) values that GA exhibited against planktonic Sh. flexneri were 2 mg/mL and 8 mg/mL. The time-kill curves showed that the concentration and the treatment time of GA led to inhibitory effects, which was evidenced by reduced cell viability, destroyed cell membranes, and changes in the bacterial morphology. GA was shown to have a significant inhibition effect on the Sh. flexneri biofilm formation and infiltrated into the EPS, which reduced the number of viable bacteria. Further studies showed that the expression of the mdoH gene and the OpgH protein was inhibited in the Sh. flexneri biofilm cells. The polysaccharide contents in the biofilm decreased. The results suggested that GA effectively inhibited planktonic Sh. flexneri activity and its biofilm formation by regulating the expression of the mdoH gene and the OpgH protein. These findings indicated that GA has potential use as a natural and a safe alternative for controlling the growth of the Sh. flexneri biofilm. Highlights: The antibacterial effect of gallic acid against planktonic Sh. flexneri was assessed. Gallic acid reduced the Sh. flexneri viability and destroyed the cell morphology. Gallic acid exhibited significant inhibition effect on Sh. flexneri biofilm formation. The expression of mdoH gene and the OpgH protein effected by gallic acid was investigated.